Pengaruh Penambahan Zat Aditif X terhadap Viskositas, Performa Mesin dan Emisi Gas Buang Sepeda Motor Honda CB150R - Senoadi, Senoadi; Adi, Supri; Permatasari, Rosyida (MESIN, 2019)
Mechanical contact is the process which can not be avoided in machinery system. The way to diminish thrist conditon which caused by the process is to give engine lubricant into that system. The lubricant resistance over the temperature system is influenced by base stock and its additives where contained of. Lubricant oil additives are chemical compounds that will improve or enhance the lubricant performance of base oil. These additives are carefully designed to ensure the functions in machines system. Engine lubricant that used in this research is MPX 1 SAE 10 W-30 and the additives that used is Engine Additive with brand Lupromax. The aim of this research is to analyze the reaction of increasing the additive EA over to viscosity and machine function of Honda All New CB 150R. In this research, it is found that the fusion with EA 5.25% (1200 ml lubricant with 63 ml additives) could: (1) reduce viscosity to 66.56 mm2/s and 9.9 mm2/s at temperatures of 40°C and 100°C, respectively, (2) enhance the torque and energy to 14.5 kW @9000 rpm and 12.23 Nm @7000 rpm with reducing the rate emision of CO to 0.44% vol, HC to 196 ppm vol, CO2 to 6.5% vol and enhancing the rate of O2 to 10.71%, and (3) reduce fuel consumption to 18.75 ml/km.